The Influence of Sundanese Cultural Values on State Civil Apparatus at the Education Office of West Java Province - Prima Setiawan; Asep Hendra (PRODI ADMINISTRASI PEMERINTAHAN DAERAH FAKULTAS MANAJEMEN PEMERINTAHAN IPDN, 2025)
Culture is one of the concepts of local wisdom that necessity to be maintained. Sundanese culture is a culture that comes from the Sundanese people. The word